Optimization of minimum crossing distance of transmission line based on multi objective ant colony algorithm. Issue 1 (1st February 2022) - Xu, Qiaoyun; Tian, Ji; Tang, Zhenpeng; Mai, Ronghuan; Qin, Yuancheng
Abstract: In the test of cross span distance of transmission line, the estimation of cross span distance is not accurate, which leads to the increase of subsequent test error. Therefore, a test method of transmission line cross span distance based on a multi-objective ant colony algorithm is proposed. Statistics of the actual information of different crossovers including trees and forest areas. Considering the transmission line as a flexible cable, the objective function for estimating the cross span distance of the transmission line is constructed according to the catenary model of the flexible cable model. On this basis, the multi-objective ant colony algorithm is used to solve the function, and the optimization results of transmission line crossing distance are output. The experimental results show that the method has high accuracy, small error, short time and reliability.